Picky eating dan ASI Ekslusif? - Javinka Fairuz Zahrani (Majority, 2021)
Picky eating is an eating disorder that is often found in toddlers. Picky eating, which is also known as fussy eating, is characterized by a child's unwillingness to try new foods as well as a very strong food preference. This of course will have a bad effect on the child because the nutritional composition of the food is not balanced. Some studies said that children with picky eating eat less protein, vegetables and fruits. However, they eat lots of sweet and fatty foods. The causes of picky eating are late introduction of food when weaning, parents who put too much pressure on their children to eat something, and the protective factor of parents who just want to give the same food over and over again. In addition, several studies have stated that the duration of breastfeeding is also one of the causes of picky eating habits. This is because breastfed babies are introduced to the various flavors of breast milk, making the transition from breast milk to complementary foods easier for children.However, because there is no consistent evidence, the conclusion is there is no relationship between the duration of exclusive breastfeeding and picky eating in toddlers.